Characterization of YSZ Coatings Deposited on cp-Ti Using the PS-PVD Method for Medical Applications - Grzegorz Dercz (MDPI AG, 2021)
A patient’s body accepting a bone implant depends not only on the biomaterial used, but also on its surface, which allows it to properly interact with bone cells. Therefore, research has focused on improving the bioactive and tribological properties of titanium and its alloys. Commercially pure titanium (cp-Ti) is widely used as a biomedical material. However, it is characterized by unsuitable tribological properties. In this work, yttria-stabilized zirconia (YSZ) was deposited on a cp-Ti substrate via plasma spray–physical vapor deposition (PS-PVD). The structural characteristics were determined using X-ray analysis (XRD). Additionally, the lattice parameters of each phase were determined using Rietveld’s method. High-resolution scanning microscopy (HR-SEM) showed a typical column structure of coatings that can be used with PS-PVD. Depending on the process parameters, the coatings differed in thickness in the range of 2.4–9.0 µm. The surface roughness also varied. The samples were subjected to nano-indenter testing. A slight change in hardness after deposition of the coating was observed, in addition to a significant decrease in the Young’s modulus. The Young’s modulus in relation to the metallic substrate was reduced to 58 or 78 GPa depending on the parameters of the spray-coating process.